Performance and Reproducibility of the Continuous Scale Physical Functional Performance 10 Test in Patients With Chronic Obstructive Pulmonary Disease: A CONTROLLED CROSS-SECTIONAL STUDY. Issue 5 (September 2018) - Stanzani, Vera; José, Anderson; de Oliveira, Cristiane Helga Yamane; Boldorini, Jacqueline Cristina; de Cordoba Lanza, Fernanda; Dal Corso, Simone; Malaguti, Carla
Abstract : Purpose: To compare the performances of patients with chronic obstructive pulmonary disease (COPD) and healthy individuals on the Continuous Scale Physical Functional Performance 10 (PFP10) test and, second, to test the reproducibility of the PFP10 test in these participants. Methods: In a prospective, cross-sectional study, 28 patients with COPD (67 ± 9 y, FEV1 : 44.3 ± 16.9% pred) and 12 healthy volunteers (healthy group) matched by age, body mass index, and sex were included. The participants performed 2 PFP10 tests 5 d apart. Main outcome measure was performance on the PFP10 test and included total score, score for specific domains, and total time to perform the PFP10 test. Results: The functional performance of patients with COPD was worse than that of the healthy group on PFP10 total scores (43.9 ± 12.6 vs 63.5 ± 9.4, respectively; P < .001; effect size: 1.78) and time to complete the tasks (207.9 ± 36.1 sec vs 153.2 ± 12.1 sec, respectively; P < .001, effect size: 2.27). In addition, the COPD group had significantly worse performance in the domains of upper-body strength, lower-body strength, balance and coordination, and endurance. The test was highly reproducible (ICC: 0.98; 95% CI, 0.96-0.99 for both groups), and the mean difference (upper and lower limits of agreement) of the total scores was −3 (−9 to 3). Conclusions: The PFP10 test is a suitable and reproducible test for determining decreases in the functional performance of patients with COPD compared with healthy individuals. Abstract : The Continuous Scale Physical Functional Performance 10 (PFP10) test was compared between patients with chronic obstructive pulmonary disease (COPD) and healthy persons, and its reproducibility was investigated. The PFP10 test is a suitable and reproducible test for determining decreases in the functional performance of patients with COPD.